THE STUDY OF THE STUDENTS’ COLLOCATION PERFORMANCE IN ARGUMENTATIVE WRITING - Haryati Oktavera (State Institute for Islamic Studies IAIN of Metro, 2014)
Collocation is used by most of the native speaker in both writing and speaking authentic English. This paper focused on knowing the students’ collocation knowledge by examining their lexical and grammatical collocation performance in their argumentative writing. This research, therefore, conducted by analyzing deeply 10 argumentative writings of the third semester students of PBI STAIN JuraiSiwo Metro in academic year 2013/2014. The result of this research showed that there were 41 % errors found in both lexical collocation (25%) and grammatical collocation (16 %) in the students’ argumentative writing. It clearly means that students’ collocation knowledge still need to be improved. Hence, teachers have an important role to play down the error in applying collocation.